An enigmatic bird from the lower Maastrichtian of Vega Island, Antarctica - Cordes Person, Amanda; Acosta Hospitaleche, Carolina Ileana Alicia; Case, Judd A.; Martin, James E. (Cretaceous Research)
We describe a partial skeleton from the lowest Maastrichtian levels of the Snow Hill Island Formation (Vega Island, West Antarctica). Because of the anatomical differences with the Antarctic Vegavis iaai and Polarornis gregorii, this fossil is recognized here as a new genus and species. The results of our phylogenetic analysis suggest that A. capelambensis would be placed inside the Ornithuromorpha, and probably nested within the Ornithurae. This provisional assignment could only be confirmed through the finding of most complete and better preserved specimens. Antarcticavis capelambensis is the geologically oldest bird described from Antarctica. Fil: Cordes Person, Amanda. North Dakota State Library; Estados Unidos Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Case, Judd A. Eastern Washington University; Estados Unidos Fil: Martin, James E. University Of Louisiana At Lafayette; Estados Unidos